REVEALING THE SPIRIT VALUE OF PRAJURU BEHAVIOR IN DISCLOSING FINANCIAL STATEMENTS AS A FORM OF ACCOUNTABILITY FOR BANJAR SEKAR SARI IN PALU CITY - Ni Made Suwitri Parwati , Nurhayati Haris, Rahayu Indriasari , Sudirman, Jurana (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to uncover the spirit of the prajuru's behavior in disclosing financial reports from Banjar Sekar Sari in the city of Palu, as a form of accountability carried out by Banjar. The Banjar organization cannot be separated from accounting. Accounting is needed as a means of management and accountability to Banjar members and to God. This research will examine how the attitudes and behavior of kelian and prajuru in disclosing financial statements are a form of their accountability to Banjar members and to God.This research is a qualitative research with an interpretive paradigm. The method of analysis used in this research is the triangulation or multi-strategy method, namely the technique of combining two or more problem-solving techniques. This research will conduct triangulation of data collection, data analysis methods, and theory construction. The research site is Banjar Sekar Sari which is located in the city of Palu. The data analysis technique in this study was carried out through three stages, namely data collection, interpretation, and reporting. Data collection was carried out by in-depth interviews and then made a manuscript to be processed and interpreted. Research shows that the attitude and behavior of the prajuru is the attitude of being obedient and obedient to religious teachings as their basis for being accountable for Banjar financial management. Being obedient and obedient to religious teachings is the same as being obedient and obedient to God or Guru Swadaya or Guru Susrusa as basic values ??in financial reporting.